Human fall control system for disabled people using double inverted pendulum - Rashid, Md. Rezaur; Shuvra, Neel Kanto Das; Roy, Raj Shekhor; Sarker, Shraboni (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.